Demonstratie tegen WAO- en Ziektewetplannen van het kabinet Lubbers/Kok op het Malieveld - Pennarts, Chris, (1991)
Demonstratie tegen WAO- en Ziektewetplannen van het kabinet Lubbers/Kok op het Malieveld.